Problematic smartphone use: A conceptual overview and systematic review of relations with anxiety and depression psychopathology - Elhai, Jon D.; Dvorak, Robert D.; Levine, Jason C.; Hall, Brian J. (Journal of affective disorders, 2017)
Research literature on problematic smartphone use, or smartphone addiction, has proliferated. However, relationships with existing categories of psychopathology are not well defined. We discuss the concept of problematic smartphone use, including possible causal pathways to such use. We conducted a systematic review of the relationship between problematic use with psychopathology. Using scholarly bibliographic databases, we screened 117 total citations, resulting in 23 peer-reviewer papers examining statistical relations between standardized measures of problematic smartphone use/use severity and the severity of psychopathology. Most papers examined problematic use in relation to depression, anxiety, chronic stress and/or low self-esteem. Across this literature, without statistically adjusting for other relevant variables, depression severity was consistently related to problematic smartphone use, demonstrating at least medium effect sizes. Anxiety was also consistently related to problem use, but with small effect sizes. Stress was somewhat consistently related, with small to medium effects. Self-esteem was inconsistently related, with small to medium effects when found. Statistically adjusting for other relevant variables yielded similar but somewhat smaller effects. We only included correlational studies in our systematic review, but address the few relevant experimental studies also. We discuss causal explanations for relationships between problem smartphone use and psychopathology. •Several causal pathways toward problematic smartphone use have been proposed in the literature.•In a systematic review of the literature, depression severity and anxiety severity were consistently related to problem smartphone use.•Stress was somewhat consistently related to problematic smartphone use.•Self-esteem was inconsistently related to problem smartphone use.